CORRELATION BETWEEN BLOOD SERUM PSA LEVEL AND MMP-2 IN PROSTATE ADENOCARCINOMA - Rahaju, Anny Setijo; Meidi, Aniek; Mastutik, Gondo; Mustokoweni, Sjahjenny; Mustika, Arifa (Indonesian Journal of Urology, 2016)
Objective: This study aims to prove the correlation between Prostate Specific Antigen (PSA) blood level and Matrix Metalloproteinase-2 (MMP-2) expression in patients with prostate adenocarcinoma. Material & method: Prostate cancer patients’ data from January 2009 to May 2012 were collected at the Department of Pathology, Soetomo General Hospital Surabaya. Data collected included patient medical documents, PSA blood examination, and histopathological examination. Histopathology slides and paraffin blocks of needle biopsies, Transurethral Resection of Prostate (TURP) and radical prostatectomy of prostate cancer patients werere-read, then the samples that met the inclusion criteria were stained by immunohistochemistry using antibodies MMP-2. Results: Data collection was done to obtain data samples of prostate cancer patients in 2009 to 2012 comprising as many as 22 patients between the ages of 52-91 years. Prostate adenocarcinoma in age of 70-79 was found in 8 patients, with a mean age of 68 years. PSA values obtained from medical documents were between 8.6-594.41 ng/ml. Spearman's test performed in this study showed a positive correlation (one-tailed) (correlation coefficient (r) 0431, p < 0.05) between blood PSA level and MMP-2 expression in patients with prostate adenocarcinoma. Conclusion: Blood PSA level correlates positively with MMP-2 expression in prostate adenocarcinoma.